VD_FINDINFO HC / 2013 / 547 vom 30. August 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, EXPULSION DE LOCATAIRE, PROCÉDURE SOMMAIRE, DEMEURE DU DÉBITEUR, IMPUTATION | 257d al. 2 CO, 86 CO, 87 CO, 257 CPC (CH)